Pelaksanaan program LINUS di sekolah rendah daerah Muar - Kadri, Roslan (2014)
Qualitative research aims to know the program for LINUS and the roles of FasiLINUS in overseeing the LINE programme in primary schools in the districts of Muar. This study also aims to look at the effectiveness of FasiLINUS in school based on its work. Respondents are the co-ordinator for LINUS and teachers who teach for LINUS in primary schools in school [SK, SJK (C) and SJKT (T)] in the District of Muar, Johor. To make strong findings, interviews conducted on the nine LINUS teachers where the research is performed. An instrument has been tested through a pilot study to determine the role of the FasiLINUS in the program LINUS and problems encountered in the programe LINUS. The findings indicate that the role of the FasiLINUS and teachers who teach implement programme for LINUS in school. In addition teachers who teach for LINUS also noted the problems encountered while teaching students in LINUS in primary schools in the districts of Muar. All suggestion about study have been discussed in chapter 5.